The Mapping Of Investor Perception On The High Financial Reporting Quality - Muljanto Siladjaja; Yuli Anwar (STIE Binaniaga, 2021)
This research mapped investor perception on high accounting information quality, particularly the accurate prediction model for future returns. The high financial reporting quality indicates the company's prospective improvement in the future under the right management. This positively affects market price fluctuation, where the investor has minimum distortion on accounting information and low risk. The obedience to accounting standards and tax regulation illustrates actual earnings in reducing agency cost's volatile movement. This study used questionnaires to gather information. The respondents were related parties with dominant influence in investment, specifically 384 samples. Through the structural equation model, the mapping of earnings quality, future market value, and dividend policy played a critical role in minimizing misleading information and improving accounting information quality. The high financial reporting quality indicates the managements' obedience in maximum implementation of regulations with continuous improvements. In this regard, the dividend policy has significantly contributed to the improvement of the earnings quality. The Decision Tree Model was used in mapping investor perception on earnings quality to estimate the high probability of a long or short position for their maximum utility. When the dividend policy is used as a mandatory indirect obligation, the management should provide high accounting information quality.